(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2025)
The article examines the main campaigns of Amir Temur, his contribution to the development of world military art, the importance of military cunning as an effective measure to achieve victory in the most important battles of Amir Temur, their influence on the development of the states of the Eurasian continent.